CHOP Potentially Co-Operates with FOXO3a in Neuronal Cells to Regulate PUMA and BIM Expression in Response to ER Stress - Arindam Ghosh; Barbara J. Klocke; Mary E. Ballestas; Kevin A. Roth (2012)
Endoplasmic reticulum (ER) stress-induced apoptosis has been implicated in various neurodegenerative diseases including Parkinson Disease, Alzheimer Disease and Huntington Disease. PUMA (p53 upregulated modulator of apoptosis) and BIM (BCL2 interacting mediator of cell death), pro-apoptotic BH3 domain-only, BCL2 family members, have previously been shown to regulate ER stress-induced cell death, but the upstream signaling pathways that regulate this response in neuronal cells are incompletely defined. Consistent with previous studies, we show that both PUMA and BIM are induced in response to ER stress in neuronal cells and that transcriptional induction of PUMA regulates ER stress-induced cell death, independent of p53. CHOP (C/EBP homologous protein also known as GADD153; gene name Ddit3), a critical initiator of ER stress-induced apoptosis, was found to regulate both PUMA and BIM expression in response to ER stress. We further show that CHOP knockdown prevents perturbations in the AKT (protein kinase B)/FOXO3a (forkhead box, class O, 3a) pathway in response to ER stress. CHOP co-immunoprecipitated with FOXO3a in tunicamycin treated cells, suggesting that CHOP may also regulate other pro-apoptotic signaling cascades culminating in PUMA and BIM activation and cell death. In summary, CHOP regulates the expression of multiple pro-apoptotic BH3-only molecules through multiple mechanisms, making CHOP an important therapeutic target relevant to a number of neurodegenerative conditions.